Effect of false ceiling on microclimatic variables of crossbred cattle during rainy season (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to find out the effect of false ceiling materials on microclimatic variables  of crossbred (Vrindavani) cattle shed during rainy season. Twenty four crossbred cattle were randomly  distributed equally into three groups (8 in each) on the basis of their average milk yield, parity and body  weight. Control group (T0) animals were kept under asbestos roof without any ceiling insulation, while  modified shed had false ceiling of Expanded Polyethylene (EPE) sheet (T1) and paddy straw thatch (T2) under  asbestos roof. The average maximum temperature was significantly (p
Keywords: Asbestos roof; Crossbred cattle and Rainy season; False ceiling; Microclimate